Diabetic Patients Knowledge, Attitudes, and Practices during the Holy Month of Ramadan: A Cross-sectional Study Conducted in Northern Border Region of Saudi Arabia - Khaled, Hayet Ben (Asian Journal of Pharmaceutics (AJP), 2025)
Fasting during Ramadan is mandatory for all Muslims who are in excellent physical and mental health. During this month, Muslims refrain from eating and drinking from sunrise to sunset. These alterations are likely to result in lower glucose management for diabetic patients. Our objective is to evaluate diabetic patient knowledge, attitudes, and practices in the Holy month of Ramadan. This cross-sectional study was carried out on a random sample of 132 diabetes patients in the Northern Border Region of Saudi Arabia over the course of 2 months (April and May 2024). An Arabic-language online survey was used to gather the data. The Statistical Packages for the Social Sciences (SPSS) software was utilized to conduct descriptive statistical analysis. Among the included sample, there were 39% males and 61% females, 36% were in the age group (36–45 years) and 27% were in the age group (26–35 years). Participants with an university education or higher represented 82%. Those who are married represented 68%. The mean score of participants for the knowledge section was 66%. For the attitude section, it was 66% and for the practice section, it was 81%. In conclusion, there is a significant knowledge and practice gap among diabetes patients about several aspects of their illness that need to be addressed when fasting during the Holy month of Ramadan. Patients with diabetes must take part in pre-Ramadan training courses.